Pengaruh Content Marketing, Price Perception dan Influencer terhadap Impulsive Buying Gen-Z di Destinasi Wisata Kuliner (Studi Kasus G-Walk Surabaya) - Aiko, Lorenzia (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
This study aims to examine the influence of content marketing, price perception, and influencers on impulsive buying behavior among Generation Z at culinary tourism destinations, with a case study at G-Walk. The population in this research consists of Generation Z individuals (born between 1995–2012) aged 16–26 years, who are active users of social media platforms and have seen content related to G-Walk Surabaya. Data collection was carried out through an online questionnaire with closed-ended questions using a 5-point Likert scale. The research sample consisted of 200 respondents, determined based on Lemeshow's formula. The collected data were analyzed using SPSS through a series of validity tests, reliability tests, classical assumption tests, as well as hypothesis testing and coefficient of determination analysis. The results show that content marketing, price perception, and influencers significantly affect the impulsive buying behavior of Generation Z at the G-Walk culinary tourism destination. These findings highlight the importance of relevant content marketing strategies, competitive price perception, and influencer involvement in driving impulsive buying decisions among Generation Z. This study contributes to understanding effective marketing factors to enhance the attractiveness of culinary tourism destinations. Keywords: content marketing, price perception, influencer; culinary, impulsive buying, generation Z